Siderophore-inspired nanoparticle-based biosensor for the selective detection of Fe3+. Issue 2 (12th November 2014) - Phillips, Daniel J.; Davies, Gemma-Louise; Gibson, Matthew I.
Abstract : Au nanoparticles modified with catechol-functionalised polymers provide a strong optical response which is highly specific to Fe 3+ ions at physiologically relevant concentrations. Abstract : Inspired by nature's exploitation of the 1, 2-dihydroxybenzene unit (or catechol) in mammalian and bacterial siderophores, we report the first example of a nanoparticle sensing system that utilises the strong catechol–Fe 3+ binding motif to trigger nanoparticle aggregation, promoting a powerful optical response. Gold nanoparticles are functionalised with RAFT polymerisation-prepared water-soluble poly( N -hydroxyethyl acrylamide) containing a catechol moiety at the α-chain-end. A strong red-to-purple colorimetric response occurs in the presence of Fe 3+ at serum concentrations (8–25 μM) in saline solution. Sodium chloride is critical in generating a strong optical output, as is the length of polymer used to coat the AuNPs. This behaviour is also demonstrated to be selective for Fe 3+ over a host of other biologically relevant ions.